If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.2 + -1q = 9q Solving -0.2 + -1q = 9q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-9q' to each side of the equation. -0.2 + -1q + -9q = 9q + -9q Combine like terms: -1q + -9q = -10q -0.2 + -10q = 9q + -9q Combine like terms: 9q + -9q = 0 -0.2 + -10q = 0 Add '0.2' to each side of the equation. -0.2 + 0.2 + -10q = 0 + 0.2 Combine like terms: -0.2 + 0.2 = 0.0 0.0 + -10q = 0 + 0.2 -10q = 0 + 0.2 Combine like terms: 0 + 0.2 = 0.2 -10q = 0.2 Divide each side by '-10'. q = -0.02 Simplifying q = -0.02
| X*.05833333333=(X-113) | | N^7/10 | | 2g+3G=10 | | 4(-y+2)=-1 | | X/3=70 | | N^10/7 | | 2m+-3m-8=26 | | Px+Q=X+1 | | 2x+4(2x+8)=10x+32 | | 1+8x^2+x^4= | | 90=(4x+12)+(6x+8) | | 4In(2x+3)=11 | | .15x+x=97.75 | | 4m+m=-90 | | (x+12)(x-7)=0 | | [8x]=28 | | .25(x+4)=41 | | 7/6=x/5 | | (7/28)=(3/x) | | 3x+24=4-10 | | 3(a+1)=5(a-1) | | x^3-2x^2-09+18=0 | | -112/16 | | 5x(3x-5)(x+1)=0 | | y=e^2x+17 | | Y=2x+a | | (9a-3)/3 | | Bj+m=j | | 16[x-3]=-80 | | 3d+2=12 | | X*.0147=(X-67) | | 11=3u-13 |